2016
DOI: 10.3233/ch-151965
|View full text |Cite
|
Sign up to set email alerts
|

The effect of centrifugation at various g force levels on rheological properties of rat, dog, pig and human red blood cells

Abstract: Abstract. Laboratory investigations often require centrifugation of blood samples for various erythrocyte tests. Although there 8 is a lack of data about the effect of centrifugation at various g force levels on erythrocyte rheological properties. We aimed 9 to investigate the effect of a 10-minute centrifugation at 500, 1000 or 1500 g at 15• C of rat, dog, pig and human venous 10 (K3-EDTA, 1.5 mg/ml) blood samples. Hematological parameters, erythrocyte deformability, cell membrane stability, osmotic 11 gradie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
0
10
1
Order By: Relevance
“…High speed centrifugation with or without contact with Percoll used for RBC fractionation was shown to impact RBC properties by causing swelling and the corresponding shift in O_min and O_hyper (Figures 2Aa,Ab; Wiegmann et al, 2017). While we did not see a decrease of EI_max (Figure 2Ac), the others have reported a drop in EI_max after centrifugation (Nemeth et al, 2015;Kiss et al, 2016;Wiegmann et al, 2017). These observations make us question the feasibility of translation of the properties reported for the age-matched RBC after fractionation to the in vivo conditions.…”
Section: Word Of Caution and Limitations Of This Studycontrasting
confidence: 71%
“…High speed centrifugation with or without contact with Percoll used for RBC fractionation was shown to impact RBC properties by causing swelling and the corresponding shift in O_min and O_hyper (Figures 2Aa,Ab; Wiegmann et al, 2017). While we did not see a decrease of EI_max (Figure 2Ac), the others have reported a drop in EI_max after centrifugation (Nemeth et al, 2015;Kiss et al, 2016;Wiegmann et al, 2017). These observations make us question the feasibility of translation of the properties reported for the age-matched RBC after fractionation to the in vivo conditions.…”
Section: Word Of Caution and Limitations Of This Studycontrasting
confidence: 71%
“…With DLA, sufficient CTCs could be isolated to allow for diagnostic tests and tumor typing to be performed. As shown in our study and others, complications associated with DLA are mild and rare, making it an easily tolerable procedure even for NSCLC patients [39][40][41][42] The number of included patients in our study was relatively small and heterogeneous in stage and treatment line. However, previous studies have shown that the number of CTCs is not influenced by these patient characteristics, and any influence of patient characteristics is accounted for since the comparisons were performed for each patient in a matched manner.…”
Section: Discussionmentioning
confidence: 83%
“…CTC detection has been increased by DLA in prostate and breast cancer patients before, but only small volumes of DLA product were processed [9][10][11]38]. DLA is a well-tolerable procedure, even in our NSCLC population, and has few complications, while placing minimal burden (only two hours of time) on patients [39][40][41][42]. Also the calculated efficacy of our procedures in isolating mononuclear cells (MNCs) was shown to be comparable with that of isolating stem cells, and DLAs in breast cancer patients [8][9][10][11]43].…”
Section: Discussionmentioning
confidence: 99%
“…We did not detect differences in the effect of relatively low TBHP concentrations after In our recent in vivo study on rats [29], there was no apparent effect of AMF on hematological parameters and, of particular note, there was no effect on the number and average In the context of aerospace travel, arguments could be given against the use of rat erythrocytes instead of human erythrocytes in experimentation. Indeed, there are differences in membrane properties of erythrocytes in these two species, such as erythrocyte deformability, cell membrane stability, osmotic gradient ektacytometry (osmoscan) and aggregation tendency [30][31][32].…”
Section: Discussionmentioning
confidence: 99%